Improved tree structure anti-collision algorithm of RFID - Xue WANG; Zhi-hong QIAN; Xiao-hui LIU; Chao CHENG (Tongxin xuebao)
The whole big query tree is divided into several branches,and the work of tag recognition is executed in each branch,thus reducing the probability of tag collision.The proposed algorithm can be divided into prefix determination and branch query two phases.In the prefix determination phase,the prefix of every tag is identified,and each prefix denotes a branch.Traverse each branch by turns to recognize tags; in the branch query phase,backward search strategy and dynamic search method are used.Theoretical analysis and simulation experiment show that when the improved algorithm can improved the overall performance of RFID system from the aspects of the number of queries,time delay,and throughput.